Micrometer controlled x-y test-table for Rockwell hardness machine / Ahmad Azmi Murad Abd. Jalil - Abd. Jalil, Ahmad Azmi Murad (1987)
The Rockwell Hardness Testing Machine that we have now is only suitable for testing small specimens. However sometimes we need to test long specimens especially as in the case the Jominy Test which is included in Metallurgy course in Semester 3. The Jominy Bar.1 in diameter by 4 in. long, is austenitized, water – quenched on one end, and then tested for hardness along its length.